A surgeon's guide to writing and publishing - Schein, Moshe; Farndon, J.; Fingerhut, Abe (Tfm Pub., 2001)
This book is aimed specifically at surgeons who wish to have their work, observations, novel ideas to be published, but do not know the route leading to successful publication in the various leading and reputable journals. Each chapter (21 in total) will attempt to guide the budding writer, using simple and brief language and taking examples from daily life.